Do stress and anxiety in early pregnancy affect the progress of labor: Evidence from the Wirral Child Health and Development Study. (5th February 2021) - Slade, Pauline; Sheen, Kayleigh; Weeks, Andrew; Wray, Susan; De Pascalis, Leonardo; Lunt, Karen; Bedwell, Carol; Thompson, Belinda; Hill, Johnathan; Sharp, Helen
Abstract: Introduction: Despite widespread belief that anxiety causes longer labor, evidence of association is inconsistent. Data gathered as part of a prospective epidemiological longitudinal study were used to investigate associations between antenatal anxiety and pregnancy‐specific stress, and labor progression was assessed by duration and use of augmentation. Material and methods: Pregnant primiparous women completed measures for anxiety and pregnancy‐specific stress at 20 weeks' gestation (n = 1145). Birth outcome data were extracted from medical records. Regression analyses and a path analysis assessed associations between antenatal anxiety and pregnancy‐specific stress, and indices of labor progression (labor duration and augmentation). Results: Anxiety/pregnancy‐specific stress were not directly associated with duration of stage 1 labor (HIGH/LOW anxiety: mean difference = 13.94 minutes, SD = 20.66, 95% CI −26.60 to 54.49, P < .50)/(HIGH/LOW pregnancy‐specific stress: mean difference = 12.05 minutes, SD = 16.09, 95% CI −19.52 to 43.63, P < .45). However, anxiety/pregnancy‐specific stress were associated with epidural use (HIGH/LOW anxiety: 39% vs 31%, P < .042; HIGH/LOW pregnancy‐specific stress: 38% vs 29%, P < .001), which was itself associated with longer labor (mean difference: 158.79 minutes, SD = 16.76, 95% CI 125.89‐191.68, P < .001). Anxiety and pregnancy‐specific stress were associated with increased likelihood of augmentation but these associations were nonsignificant after accounting for epidural, which was itself highly associated with augmentation. However, path analysis indicated an indirect effect linking pregnancy‐specific stress, but not general anxiety, to labor duration and augmentation: elevated pregnancy‐specific stress led to greater use of epidural, which was linked to both increased rates of augmentation, and increased labor duration. Conclusions: Contrary to general belief, general anxiety and specific pregnancy stress were not directly linked to longer duration of stage one labor. However specific pregnancy stress was associated with epidural use, which in turn was significantly associated with risk of augmentation, and longer stage one labor. Identification of pregnancy‐specific stress could help to identify women for whom psychological interventions could improve birth experience.